Pengaruh Gaya Belajar Terhadap Hasil Belajar Siswa Kelas XI di SMAN 1 Gresik - Safianti, Siti Dina (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
Learning activities are the core of the overall educational process, involving two active actors, namely teachers and students. In this case, learning style is one of the main keys that determines the effectiveness of teaching and learning activities. This study aims to explain the influence of learning styles on the learning outcomes of class XI students at SMAN 1 Gresik. This study uses a quantitative method by taking the research location at SMAN 1 Gresik. Primary data in this study were obtained through research instruments in the form of questionnaires with a Likert scale. The population in this study was class XI students at SMAN 1 Kota Gresik. The results of this study indicate that there is a significant positive influence between learning styles on the learning outcomes of class XI students at SMAN 1 Gresik, which is 0.469 or 46.9% with a significance level of 0.00 (<0.05).